Characterization of marine heat waves in the eastern tropical Atlantic Ocean - Djakouré, Sandrine; Koné, Mamadou; Koffi, Kouakou Urbain; Kouadio, Kouassi Yves; Adon, Marcellin; Nyadjro, Ebenezer; Ta, Samuel (Frontiers in Marine Science, 2023)
Marine heat waves (MHWs) can potentially alter ocean ecosystems with far-reaching ecological and socio-economic consequences. In this study, we characterize the MHWs in the eastern tropical Atlantic Ocean with a focus on the Gulf of Guinea (GG). The Optimum Interpolation Sea Surface Temperature (OISST) data from January 1991 to December 2020 and PIRATA network temperature data, from October 2019 to March 2020, have been used for this purpose. The results show that the eastern tropical Atlantic has experienced an annual average of 2 MHWs events in recent decades. Based on the spatial distribution of the different characteristics of these MHWs, we subdivided the eastern tropical Atlantic Ocean into three zones: the northern coast of the GG, the equatorial zone and the Congo-Gabon coastal region. The trend associated with MHWs events showed an increase in the number of MHWs since 2015 in the different zones. This increase was greater at the northern coast of the GG than at the equator and the Congo-Gabon coast. Long-duration MHWs are more frequent in the equatorial zone. High intensity MHWs were observed in different areas with sea surface temperature anomalies greater than 2°C. These anomalies are more intense at the Congo-Gabon coast. The results also revealed that the MHWs event at the equator from mid-October 2019 to March 2020 initially occurred in the subsurface before it appeared at the surface. These results also suggested that ocean temperatures are a potential predictor of MHW events.